A Content Analysis of Papers Published by the Lecturers of the Faculty of Sport and Physical Education for the Last Three Years in Journal of Anthropology of Sport and Physical Education - Dragan Bacovic (Journal of Anthropology of Sport and Physical Education, 2019)
Journal of Anthropology of Sport and Physical Education (JASPE) is a scientifi c journal that exists for three years and has so far released 107 scientifi c papers in 7 editions. Papers of lecturers from Faculty for sport and physical education were classifi ed in this paper by the method of content analysis. In last three years they have published 69 papers in total which are classiffi ed in this paper by these areas: anthropology, sports marketing, papers which analyze the content and other papers. The most published papers are from area of anthropology, 35 in total. This research can be useful for further theoretical research, as well as for theoreticians.